Penerapan Metode Scrum Pada Perancangan Sistem Informasi Manajamen Arsip Surat Berbasis Web - Nilawati, Lala; Widya, Sekar Ayu (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
Abstracts are written in English and Indonesian (except articles written in English) which contain the main issues, research objectivesArchives are a source of information that plays an important role in supporting the administration and management activities of an agency. This research focuses on designing a web-based local government letter archive management information system for the East Jakarta Cipta Karya, Spatial Planning and Land Affairs Agency (SDCKTRP). Currently data collection on incoming and outgoing mail archival documents and reporting is still using the manual method, with excessive use of paper or inefficient use of storage space, so it takes a long time to obtain the desired data. The application of a mail archive management information system is a solution to the problems that exist in SDCKTRP. The research method used in making this system design is by applying the scrum method, and applications built using the Codeigniter framework and using the MySQL database. This computerized letter archive management information system can make it easier to process data and the data storage process will be more neatly arranged, because it is stored in a database so that it can prevent data loss.